A qualitative study of peer education experiences and oral pre-exposure prophylaxis use among adolescent girls and young women at high risk of HIV acquisition in Kampala, Uganda - Mayanja, Yunia; Kayesu, Ivy; Nabalwanyi, Zam; Kosidou, Kyriaki; Ekstrom, Anna Mia; Mujumbusi, Lazaaro; Rutakumwa, Rwamahe (Frontiers in Public Health, 2025)
IntroductionOral pre-exposure prophylaxis (PrEP) use remains low among adolescent girls and young women (AGYW) at high HIV risk in Eastern and Southern Africa. Most peer-led interventions involve brief interaction, however peer education offering extended engagement may foster peer learning. This study explored experiences of a peer education intervention among AGYW who engaged in sex work (young FSWs) in Kampala, Uganda and examined how it influenced PrEP use.MethodsFrom January 2023 to February 2024, we conducted in-depth interviews (IDIs) with AGYW aged 14–24, purposively sampled from a randomized trial assessing the effect of peer education on PrEP uptake and adherence. We conducted 18 baseline IDIs to assess prior PrEP knowledge and peer education experiences, and 17 follow-ups to explore experiences of the intervention. IDIs were audio-recorded, transcribed, coded (NVivo 14) using an inductive approach. Baseline IDIs were analysed thematically and follow-ups interpreted using the situated Information-Motivation-Behavioural Skills (sIMB) model of behaviour change.ResultsAt baseline, AGYW had varying PrEP knowledge, no prior peer education experience and negative community perceptions hindered PrEP use. All those uninterested in PrEP at baseline did not initiate it. After the intervention, participants reported improved knowledge, motivation, and behavioural skills, though contextual barriers persisted. Peer education conveyed accurate information and dispelled myths. Motivation to use PrEP stemmed from HIV risk awareness, positive experiences and attitudes regarding PrEP use, peer influence and peer-led psychosocial support. AGYW gained behavioural skills to incorporate PrEP in daily routines, use it discreetly and maintain adherence when travelling. Non-disclosure of PrEP use was commonly used to mitigate barriers to PrEP use. Persistent contextual barriers included high mobility, concurrent use or prior negative experiences with other oral medication, stigma, partner disapproval and partner violence. Peer leader competence and confidentiality were initial concerns although no incidents were reported. AGYW preferred accessing PrEP at private, nearby facilities providing adequate health education.DiscussionIntegration of peer education into PrEP programs is recommended, alongside strategies addressing contextual barriers—such as improving access in remote areas, adequate counselling when taking other oral medications, community education, partner violence prevention, and subsidies for long-acting PrEP for those unable to maintain daily use.